Whole-Genome Sequencing Reveals Exonic Variation of ASIC5 Gene Results in Recurrent Pregnancy Loss - Al Qahtani, Nourah H.; AbdulAzeez, Sayed; Almandil, Noor B.; Fahad Alhur, Norah; Alsuwat, Hind Saleh; Al Taifi, Hatoon Ahmed; Al-Ghamdi, Ahlam A.; Rabindran Jermy, B.; Abouelhoda, Mohamed; Subhani, Shazia; Al Asoom, Lubna; Borgio, J. Francis (Frontiers in Medicine, 2021)
Family trio next-generation sequencing based variant analysis was done to identify the genomic reason on unexplained recurrent pregnancy loss (RPL). A family (dead fetus & parents), from Saudi Arabia, has earlier history of three unexplained RPL at the 9th week of pregnancy was included in the study. Whole genome sequencing (WGS) sequencing of dead fetus and its parents were done to identify the pathogenic variation and confirmed through Sanger sequencing. WGS of dead fetus identifies a novel homozygous exonic variation (NM_017419.3:c.680G>T) in ASIC5 (acid sensing ion channel subunit family member 5) gene, the parents are heterozygous. Newly designed ARMS PCR followed by direct sequencing confirms the presence of heterozygous in one subject and absence of homozygous novel mutation among randomly selected healthy Saudis. The second family with heterozygous was confirmed with three unexplained RPL. Pathogenicity analysis of R227I amino acid substitution in ASIC5 protein through molecular docking and interaction analysis revealed that the mutations is highly pathogenic, decrease the stability of the protein and prevents binding of amiloride, which is an activator to open ASIC5’s acid sensing ion channel. The identified rare and novel autosomal recessive mutation, c.680G>T:p.R227I (ASIC5Saudi) in two families confirm ASIC5 gene association with RPL and can be fatal to the fetus.